1982
DOI: 10.1029/jc087ic11p09003
|View full text |Cite
|
Sign up to set email alerts
|

Threshold friction velocities and rupture moduli for crusted desert soils for the input of soil particles into the air

Abstract: Desert soils having clay crusts, mostly from the Mojave Desert, were tested for threshold friction velocity (the friction velocity at which soil erosion begins) with an open-bottomed wind tunnel. The soils were also tested for content of clay, water-soluble material, calcium carbonate, organic material, mineralogy of clay and of salts, soil moisture, modulus of rupture, and crust thickness. If no loose material existed on the soil surface, crusts having modulus of rupture greater than 0.7 bar and crust thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
2
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(146 citation statements)
references
References 9 publications
8
135
2
1
Order By: Relevance
“…On average, 40 measurements of the surface strength were taken at 0.25 m intervals across the width of each test section, at two locations in each section. This measurement is similar to, but not an exact replication of, the modulus of rupture test used by Gillette et al 17 to assess the strength of desert soil crusts.…”
Section: Pm 10 Samplingmentioning
confidence: 55%
See 1 more Smart Citation
“…On average, 40 measurements of the surface strength were taken at 0.25 m intervals across the width of each test section, at two locations in each section. This measurement is similar to, but not an exact replication of, the modulus of rupture test used by Gillette et al 17 to assess the strength of desert soil crusts.…”
Section: Pm 10 Samplingmentioning
confidence: 55%
“…The BS, PE, and PEP suppressants were applied to Fields Road during July [13][14][15][16][17][18]1995, and the NHCO was applied during October 17-19, 1995. A fifth section was left untreated for comparison of PM 10 emissions with those from the treated sections.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It is true that SO4 = can be highly enriched in certain soils; for example, gypsum crusts are found in some arid environments. However, these crusts are believed to be resistant to deflation [Gillette et al, 1982]. Glaccum, in a study of the mineralogy of dusts collected at Barbados, did find gypsum, but it was shown to be a reaction product formed on the filter; African dust samples collected aboard aircraft above the MBL did not contain gypsum [Glaccum, 1978;Glaccum and Prospero, 1980].…”
Section: Size Distributionsmentioning
confidence: 99%
“…WEMO predicts horizontal dust flux (gÁcm À1 Ád À1 ) on the basis of wind velocity, plant height, the size-class distribution of gaps between plant canopies, total plant cover, threshold shear velocity (TSV; Gillette et al 1982), and a suite of other variables. TSV is the surface wind velocity required to initiate soil movement and thus is a measure of soil erodibility.…”
Section: Simulation Modelingmentioning
confidence: 99%